Airway microbiome in adult survivors of extremely preterm birth: the EPICure study. Issue 1 (10th January 2019) - Rofael, Sylvia A.D.; McHugh, Timothy D.; Troughton, Rachael; Beckmann, Joanne; Spratt, David; Marlow, Neil; Hurst, John R.
Bronchopulmonary dysplasia (BPD) is a major complication of preterm birth that leads to lifelong respiratory morbidity. The EPICure study has investigated the longitudinal health outcomes of infants born extremely preterm (EP; <26 weeks gestation). Our aim was to characterise the airway microbiome in young adults born extremely preterm, with and without neonatal BPD, in comparison to matched term-born controls. Induced sputum was collected from 92 young adults aged 19 years (51 EP and 41 controls). Typical respiratory pathogens were detected using quantitative PCR. 16S rRNA gene sequencing was completed on 74 samples (29 EP with BPD; 9 EP without BPD; and 36 controls). The preterm group with BPD had the least diverse bacterial communities. The relative abundance of Bacteriodetes, particularly Prevotella melaninogenica was significantly lower in the preterm group compared to controls. This decline was balanced by a nonsignificant increase in Firmicutes . Total Prevotella relative abundance correlated with forced expiratory volume in 1 s z-score (ρ=0.272; p<0.05). Typical respiratory pathogen loads and prevalence were similar between groups. In conclusion, extremely preterm birth is associated with a significant dysbiosis in airway microbiome in young adulthood regardless of neonatal BPD status. This is characterised by a shift in the community composition away from Bacteriodetes as manifested in a significant drop in Prevotella relative abundance. For the first time we demonstrated that extremely preterm birth results in significant dysbiosis in the airway microbiota in early adulthood which correlated with FEV 1 as a clinical parameter of obstructive lung disease http://ow.ly/PYJS30myLP0